DIAGNOSA PENYAKIT KULIT WAJAH MENGGUNAKAN METODE DECESSION TREE DAN ALGORITMA C4.5 - Abdul Aziz; Karpen Karpen (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
Today's face is something that is very much considered by both women and men. Women and men do facial treatments so often because the face is the first thing to see when meeting someone. However, there are those that often interfere with the face, one of which is a skin disease that is very diverse ranging from acne, dullness, blackheads to cancer. In fact, to overcome this, many people always consult with doctors, especially face problems. One thing that can be done is to diagnose facial skin diseases using the decession tree method and the c 4.5 algorithm. The existence of this system is expected to be a solution in conducting consultations for women and men for facial problems. By using the decession tree method and the c 4.5 algorithm and by using a number of data mining, it will give results that can be used as guidelines in treating facial skin diseases. In addition, the existence of this system will also be very helpful in the field of services to consumers, both women and men, especially for facial care to avoid facial skin diseases, which has been a problem so far.